Analisis Anggaran Belanja Makanan dalam Menentukan Standar Gizi Pasien Rawat Inap di Rumah Sakit PKU Muhammadiyah Gamping - Merita Bernik; Fanisa Putri (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2020)
This research aims to find out how to analyze the quality of the services of a services company integrated with the SERVQUAL (Service Quality) and the Kano Model into the Quality Function Deployment (QFD) in the Clinic Midwife Ides that have decreased the number of patients since 2015-2018. Data collection in the form of needs and desires of consumers (customer requirements) using a questionnaire derived from the five dimensions of SERVQUAL (Service Quality), there are tangible, reliability, assurance, responsiveness, and empathy as well as data collection technical characteristics (technical requirements) through interviews to the management of the Clinic Midwives Ides. Through a questionnaire, the consumer Clinic Midwife Ides can rate the level of importance (expectations) of each service attribute and evaluate the quality of current service delivery, and assess the level of satisfaction if these attributes are not available (Category dysfunctional Kano Model). In the questionnaire there are 22 attributes are valid and have reliability value 0,926 for the variable hope and 0,953 for the variable the fact the quality of service at this time. After that is done the calculation of the value of consumer satisfaction. There are 10 attributes with the value of the satisfaction is negative. Having obtained the category for each attribute, then find the value of adjusted importance by multiplying the weight category of the canoe with the value of customer satisfaction and level of importance. Based on the results of the interview, there are 6 technical characteristics related to the customer needs to know the needs and desires of consumers of the Clinic Midwives Ides. Quality Function Deployment (QFD) is carried out using a matrix of House of Quality (HOQ) which is integrated with the Kano Model. In this study, the 3 attributes of customer requirements as well as the attributes of the technical responses that has a percentage rate of interest above the average and should be a priority of improving the quality of service.